MAKNA DAN FUNGSI PETATAH PETITIH MELAYU DUSUN SEMPURNA ALAM DESA SEROMBOU INDAH - Preen Prayoga; Misra Nofrita (Universitas Batanghari, 2026)
This research is motivated by the fading use of oral literature, specifically “petatah-petitih,” amidst the currents of modernization and globalization in the Malay community of Sempurna Alam Hamlet, Serombou Indah Village. In fact, petatah-petitih contains noble values and local wisdom that serve as life guidelines and moral advice. The purpose of this study is to describe the forms of meaning and functions of Malay petatah-petitih in that region. The research method used is descriptive qualitative. The data in this study consist of spoken petatah-petitih obtained from traditional leaders or community elders as key informants. Data collection techniques were carried out through observation, in-depth interviews, documentation via video recording, and data transcription. Data analysis was conducted holistically through stages of identification, semantic meaning analysis, and drawing conclusions regarding its social functions. The results show that the Malay petatah-petitih of Sempurna Alam Hamlet is not merely a series of beautiful words, but a tool for moral education and social control that reflects the harmonious relationship between humans, nature, and the Creator. The preservation of this oral literature is crucial as a cultural identity for the younger generation.